2008
DOI: 10.1002/mrd.20854
|View full text |Cite
|
Sign up to set email alerts
|

Role of the major ecto‐phosphoprotein in sperm flagellar motility using a cell electroporation method

Abstract: Previous studies from our laboratory have identified MPS, a 100-kDa protein, as the major phosphoprotein substrate of caprine sperm ecto-cyclic AMP independent protein kinase. In this study the isolated (32)P-labelled MPS has been incorporated into mature caprine (Capra indicus) cauda-epididymal spermatozoa with the help of cell electroporation technique to investigate the effect of MPS on sperm flagellar motility. The optimum conditions for electroporation of sperm cells consisted of exposure of 0.2 ml of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Consequently the precise role of cytosolic protein kinases/phosphoproteins in the acrosome reaction is largely unknown. As elaborated in the “Introduction” Section, a novel protein kinase (CIK) and its endogenous membrane‐bound protein substrate (MPS) have been shown to occur on sperm head overlying the acrosome (Maiti et al, 2004, 2008; Nath et al, 2008). This study reports for the first time, the role of the well‐defined sperm surface ecto‐protein kinase and its phosphoprotein substrate in the regulation of acrosome reaction triggered by Ca ++ ionophore in vitro using the caprine sperm model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently the precise role of cytosolic protein kinases/phosphoproteins in the acrosome reaction is largely unknown. As elaborated in the “Introduction” Section, a novel protein kinase (CIK) and its endogenous membrane‐bound protein substrate (MPS) have been shown to occur on sperm head overlying the acrosome (Maiti et al, 2004, 2008; Nath et al, 2008). This study reports for the first time, the role of the well‐defined sperm surface ecto‐protein kinase and its phosphoprotein substrate in the regulation of acrosome reaction triggered by Ca ++ ionophore in vitro using the caprine sperm model.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier investigators have provided several lines of evidences for the occurrence of ecto‐protein kinases in a variety of mammalian cells (Mastro and Rosengurt, 1976; Schlaeger and Kohler, 1976; Majumder, 1981; Halder and Majumder, 1986; Dey and Majumder, 1990; Walter et al, 2000; Guthmann et al, 2002; for review Nath et al, 2008), the above‐mentioned findings from our laboratory provide confirmatory evidence for the localization of an ecto‐protein kinase and its protein substrate on a cell surface. The data demonstrate that ecto‐CIK through its substrate protein: MPS plays a vital role in the regulation of sperm forward progression and velocity (Maiti et al, 2004, 2008; Nath et al, 2008). MPS serves as a significant promoter of sperm forward progression.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thereby, it demonstrates that CIK is a unique membrane protein-specific kinase, which specifically phosphorylates serine and threonine residues of the sperm outer cellsurface phosphoproteins [35]. It was further demonstrated that ecto-CIK plays a vital role in the regulation of sperm forward progression and velocity through its substrate protein (MPS) [33][34][35][36]. The aim of this present study is to investigate the role of the phosphorylation event mediated by the CIK on the activation of forward motility in the epididymis through plasma membrane bound voltage dependent L type calcium channel.…”
Section: Introductionmentioning
confidence: 96%
“…Both CIK and MPS are localized primarily in the acrosomal cap area of the external surface of the mature sperm head as demonstrated by indirect immunofluorescence studies [4, 6]. We have demonstrated that ecto-CIK through its substrate protein (MPS) plays a vital role in the regulation of sperm forward progression and velocity [4, 5, 7]. More recent studies from our laboratory demonstrated that the sperm external surface CIK and MPS are essential for membrane fusion component of acrosome reaction [6].…”
Section: Introductionmentioning
confidence: 99%